Synthesis, cytotoxicity and anti-cancer activity of new alkynyl-gold(i) complexes. Issue 4 (21st December 2015) - De Nisi, Assunta; Bergamini, Christian; Leonzio, Marco; Sartor, Giorgio; Fato, Romana; Naldi, Marina; Monari, Magda; Calonghi, Natalia; Bandini, Marco
Abstract : Alkynyl(triphenylphosphine)gold(i ) complexes carrying variously substituted propargylic amines have been synthesized and fully characterized in solution and solid state. Abstract : Alkynyl(triphenylphosphine)gold(i ) complexes carrying variously substituted propargylic amines have been synthesized and fully characterized in solution and solid state. High levels of toxicity ( i.e. micromolar range) were recognized for a series of cancer cell lines with particular emphasis on HT29, IGROV1, HL60 and I407. In particular the lead compound3ab was identified as the most active compound in all cell lines (IC50 : 1.7–7.9 μM).